PENERAPAN MODEL PEMBELAJARAN PROBING-PROMPTING UNTUK MENINGKATKAN HASIL BELAJAR KIMIA MATERI LARUTAN PENYANGGA PESERTA DIDIK KELAS XI MIPA SMAN 12 PEKANARU - Suhendra Suhendra; Rajawali Usman Rery; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: this research aimed to increase students learning outcomes by application of learning model probing-prompting subject of buffer solution in class XI MIPA SMAN 12 Pekanbaru. This research is an experiment research with randomized control group pretest-posttest design. The sample in this research are class XI MIPA 3 as experiment class and XI MIPA 5 as control class which is determined randomly after the normality test and homogeneity test. The experiment class was treated with the application of learning model probing-prompting while the control class without the application of learning model probing-prompting. The data analysis technique to test the hypothesis was using t-test right side. Based on the data analysis, it is obtained tcount=1,71 and ttable=1,66 with α=0,05 ,dk= 77. Tcount>ttable is 1,71>1,66, its mean that the application of learning model probing-prompting can improve students learning outcomes subject of buffer solution in class XI MIPA SMAN 12 Pekanbaru.Key Word: Learning Outcomes, Probing-Prompting, Buffer Solution